2021
DOI: 10.1177/1060028020985303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metformin on Circulating Levels of Inflammatory Markers in Patients With Type 2 Diabetes: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Background: Emerging evidence indicates that metformin has anti-inflammatory effect; however, the results differ concerning randomized controlled trails of the effect of metformin on inflammatory markers in type 2 diabetes (T2D) patients. Objective: This study reassessed the data on the effect of metformin treatment on inflammatory markers in T2D patients through a systematic review and meta-analysis. Methods: A systematic search was performed in the PubMed, ISI Web of Science, EMBASE, Cochrane Library and Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…Metformin can decrease various markers of inflammation in diabetics and other disease settings, however the effect of metformin on systemic inflammation in healthy, non-prediabetic and nondiabetic older adults has not been studied in depth. Metformin has previously been shown to decrease circulating levels of CRP, IL-6, and TNF-α in patients with type 2 diabetes [ 81 ], however this finding was not replicated in our subjects who were nondiabetic and nonprediabetic. It is likely that since our subjects were quite healthy with very limited co-morbidities and frailty levels that metformin did not have a measurable effect on circulating inflammatory levels.…”
Section: Discussioncontrasting
confidence: 79%
“…Metformin can decrease various markers of inflammation in diabetics and other disease settings, however the effect of metformin on systemic inflammation in healthy, non-prediabetic and nondiabetic older adults has not been studied in depth. Metformin has previously been shown to decrease circulating levels of CRP, IL-6, and TNF-α in patients with type 2 diabetes [ 81 ], however this finding was not replicated in our subjects who were nondiabetic and nonprediabetic. It is likely that since our subjects were quite healthy with very limited co-morbidities and frailty levels that metformin did not have a measurable effect on circulating inflammatory levels.…”
Section: Discussioncontrasting
confidence: 79%
“…Furthermore, metformin inhibits TNF‐α–dependent NF‐κB inflammatory signalling, leading to decreased secretion of inflammatory cytokines like CXCL1, CXCL2, IL‐1β, and IL‐6 8 . Consistent with this, metformin has been shown to reduce subclinical inflammation (measured by the neutrophil to lymphocyte ratio [NLR]) and C‐reactive protein concentrations in T2D 8,24,25 . In accordance with these anti‐inflammatory effects, preadmission metformin use was associated with reduced mortality among medical and surgical intensive care patients with T2D 26 .…”
Section: Discussionmentioning
confidence: 64%
“…21 For these reasons, it is an ideal therapy for randomized controlled trials (RCTs) in the face of the ongoing COVID- ) and C-reactive protein concentrations in T2D. 8,24,25 In accordance with these anti-inflammatory effects, preadmission metformin use was associated with reduced mortality among medical and surgical intensive care patients with T2D. 26 The This study also suffers the limitations characteristic of administrative databases.…”
Section: Discussionmentioning
confidence: 99%
“…According to the US Diabetes Prevention Study, this drug results in diminishing CRP levels in individuals suffering from impaired glucose tolerance (20). The results of recent research have suggested the anti-inflammatory effect of metformin on patients with T2D (21). Some researchers, in a systematic review, reported CRP as the highest effect of metformin on lowering inflammatory factor levels in type 2 diabetic individuals, thus the value of this factor diminishes significantly (21).…”
Section: Discussionmentioning
confidence: 99%